A Virtual-Reality Edu-Game: Save The Environment from the Dangers of Pollution - Dita Aluf Mawsally; Endah Sudarmilah (Department of Informatics, Universitas Muhammadiyah Surakarta, Indonesia, 2019)
The virtual reality educational game, with theme “saving the environment from the danger of pollution” – aims to help children aged 10-13 years in understanding pollution and how to reduce it. The game uses smartphone and VR Box. This edu game is designed under SDLC (Software Development Life Cycle) of the waterfall model. Contained assets are obtained from the Unity Asset Store which will simulate learning techniques with several educational games. This can be seen as an advantage from the traditional learning method. Based on a black box test, this game runs well on target devices. Usability test is conducted using the System Usability Scale (SUS), and this game gets a score of 71.58 which is in the